High-Throughput Imaging of Blood Flow Reveals Developmental Changes in Distribution Patterns of Hemodynamic Quantities in Developing Zebrafish - Maung Ye, Swe Soe; Kim, Jung Kyung; Carretero, Nuria Taberner; Phng, Li-Kun (Frontiers in Physiology, 2022)
Mechanical forces from pressurized blood flow (hemodynamic forces) contribute to the formation and shaping of the blood vascular network during embryonic development. Previous studies have demonstrated that hemodynamic forces regulate signaling and gene expression in endothelial cells that line the inner surface of vascular tubes, thereby modifying their cellular state and behavior. Given its important role in vascular development, we still know very little about the quantitative aspects of hemodynamics that endothelial cells experience due to the difficulty in measuring forces in vivo. In this study, we sought to determine the magnitude of wall shear stress (WSS) exerted on ECs by blood flow in different vessel types and how it evolves during development. Utilizing the zebrafish as a vertebrate model system, we have established a semi-automated high-throughput fluorescent imaging system to capture the flow of red blood cells in an entire embryo between 2- and 6-days post-fertilization (dpf). This system is capable of imaging up to 50 embryos at a time. A semi-automated analysis method was developed to calculate WSS in zebrafish trunk vessels. This was achieved by measuring red blood cell flow using particle tracking velocimetry analysis, generating a custom-made script to measure lumen diameter, and measuring local tube hematocrit levels to calculate the effective blood viscosity at each developmental stage. With this methodology, we were able to determine WSS magnitude in different vessels at different stages of embryonic growth and identified developmental changes in WSS, with absolute levels of peak WSS in all vessel types falling to levels below 0.3Pa at 6 dpf. Additionally, we discovered that embryos display an anterior-to-posterior trend in WSS at each developmental stage.